Phytophthora acerina sp. nov., a new species causing bleeding cankers and dieback of Acer pseudoplatanus trees in planted forests in northern Italy. (28th November 2013) - Ginetti, B.; Moricca, S.; Squires, J. N.; Cooke, D. E. L.; Ragazzi, A.; Jung, T.
<x xml:space="preserve">Abstract</x> A severe dieback of Acer pseudoplatanus trees was noticed in planted forest stands in northern Italy in 2010. Affected trees showed collar rot and aerial bleeding cankers along the stems, leading to crown dieback and eventually death. An unknown Phytophthora species was consistently isolated from necrotic bark and xylem tissue and from rhizosphere soil. Based on its unique combination of morphological and physiological characters and phylogenetic analysis, this new taxon is here described as Phytophthora acerina sp. nov. Phylogenetic analysis of ITS, cox1 and β‐tubulin gene regions demonstrated that P. acerina is unique and forms a separate cluster within the 'P. citricola complex', closely related to P. plurivora. Phytophthora acerina is homothallic with smooth‐walled oogonia, thick‐walled, mostly aplerotic oospores with a high abortion rate, paragynous antheridia, and persistent, morphologically variable semipapillate sporangia. Four to 5‐week‐old cultures produced globose to subglobose, appressoria‐like and coralloid hyphal swellings and characteristic stromata‐like hyphal aggregations. Optimum and maximum temperatures for growth are 25°C and 32°C, respectively. Genetic uniformity of all 15 studied isolates and the apparent absence of this species in the extensive surveys of nurseries, forests and seminatural ecosystems conducted in the previous two decades across Europe indicate a recent clonal introduction to northern Italy. Under‐bark inoculation tests demonstrated high aggressiveness of P. acerina to A. pseudoplatanus indicating that this pathogen might be a serious risk to maple plantations and forests in Europe.